General Public Preferences for Allocating Scarce Medical Resources During COVID-19 - Huseynov, Samir; Palma, Marco A.; Nayga, Rodolfo M. (Frontiers in Public Health, 2020)
COVID-19 has overwhelmed healthcare systems across the globe with an unprecedented surge in the demand for hospitalizations. Consequently, many hospitals are facing precarious conditions due to limited capacity, especially in the provision of ventilators. The governing ethical principles of medical practice delineated in Emanuel et al. (2020) favor prioritizing younger patients, largely because their relatively higher expected life years. We conduct a survey with the general public in the United States to elicit their preferences for the allocation of a limited number of ventilators. The results show that the general public views align with the established ethical principles, which favor younger patients.